(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The ability to improve its products, services, work procedures and to innovate continuously has become crucial for any organization. The higher education sector is always fueled by ever-growing demand for capabilities and competencies and for institutions to thrive in this highly competition driven era, they must respond in novel ways to meet this demand. Amidst stiff competition, swift advances in new technologies and changing needs of the international labor markets, the sector itself presents a fertile ground for pioneering innovations. Therefore, the institutions must understand how innovations are developed and how employees’ work behaviour is related to this process. The present study tries to examine the relationship between Psychological Capital and Social Capital as influencers of Innovative Work Behaviour of the teaching professionals of this sector in Assam.